Large-scale chromatin organization of the major histocompatibility complex and other regions of human chromosome 6 and its response to interferon in interphase nuclei. - Volpi, E; Chevret, E; Jones, T; Vatcheva, R; Williamson, J; Beck, S; Campbell, R; Goldsworthy, M; Powis, S; Ragoussis, J; Trowsdale, J; Sheer, D (2000)
The large-scale chromatin organization of the major histocompatibility complex and other regions of chromosome 6 was studied by three-dimensional image analysis in human cell types with major differences in transcriptional activity. Entire gene clusters were visualized by fluorescence in situ hybridization with multiple locus-specific probes. Individual genomic regions showed distinct configurations in relation to the chromosome 6 terrritory. Large chromatin loops containing several megabases of DNA were observed extending outwards from the surface of the domain defined by the specific chromosome 6 paint. The frequency with which a genomic region was observed on an external chromatin loop was cell type dependent and appeared to be related to the number of active genes in that region. Transcriptional up-regulation of genes in the major histocompatibility complex by interferon-gamma led to an increase in the frequency with which this large gene cluster was found on an external chromatin loop. Our data are consistent with an association between large-scale chromatin organization of specific genomic regions and their transcriptional status.